Comunicación oral y su incidencia en el rendimiento escolar de los niños y niñas de la Escuela de educación básica "Leónidas Plaza Gutiérrez" del cantón Baba, Provincia de Los Ríos, Periodo 2014-2015, Taller de capacitación. - Haz Bustamante, Marcia Francisca (2014)
This research entitled ORAL COMMUNICATION AND ITS IMPACT ON SCHOOL PERFORMANCE OF THE CHILDREN OF BASIC EDUCATION SCHOOL "LEONIDAS PLAZA" BABA CANTON PROVINCE OF LOS RÍOS PERIOD 2014-2015. A high rate of children with problems in the development of the language as the improper pronunciation of words, was identified alterations in the verbal articulation, phonology disorders, stuttering. These problems affect the communication of ideas such as understanding and interpretation as well as the issue of oral language preventing the understanding, understanding with people in the environment in which they develop. In the classroom practice in oral communication technique presented in great difficulty when students articulate syllables and words, affecting the process of literacy especially the mispronunciation of words by frequent repetition and prolongation of sounds and syllables, too he shortened the silence is not speaking in specific situations, for fear of the unknown to any activity to be performed in the process of information. The goal and the hypotheses is evaluate the impact of Oral Communication in the School Achievement Boys and Girls Basic Education School Leonidas Plaza. The changes are intended to improve communication and interaction between the educational communities and help the work of teachers, improving the development of linguistic skills necessary tools and achieve a knowledge autonomously and incorporating methodological, playful strategies. A proposal is developed through a training workshop communicative teaching materials for students of basic education school Leonidas Plaza and improve all existing gaps and facilitate the development of good oral communication in the process of teaching and learning.